Método alternativo de purificação do vírus do mosaico-comum do feijoeiro - Maciel Zambolim, Eunize; de Carvalho , Murilo Geraldo; Matsuoka, Kiyoshi (Revista Ceres, 2025)
Bean common mosaic virus, a potyvirus, was purified employing borate butter at moderately high pH, in the extraction, and thereafter, in the presence of urea and 2-mercaptoethanol to prevent particle aggregation.